The real Cassian revisited : monastic life, Greek Paideia, and Origenism in the sixth century - Tzamalikos, P. 1951- (Vigiliae Christianae, Supplements, 2012)
This is a critical analysis of texts included in Codex 573 (ninth century, Monastery of Metamorphosis, Meteora, Greece), which are published along with the present volume, in the same series. The Codex, entitled 'The Book of Monk Cassian the Roman', reveals a sixth-century heretofore unknown intellectual, namely, Cassian the Sabaite, native of Scythopolis, being its real author. By means of Medieval forgery, he has been eclipsed by a figment currently known as 'John Cassian of Marseilles', native of Scythia. Exploration reveals critical aspects of the interplay between Hellenism and Christianity, the Origenism and pseudo-Origenism of the sixth century, and Christian influence upon Neoplatonism in Late Antiquity. Cassian the Sabaite is probably the last great representative of a prolonged fruitful autumn of Late Antique Christian scholarship, who saw Hellenism as a treasured patrimony to draw on, rather than as a demon to be exorcised -which resulted in his 'second death'(Rev. 2,11). Two edition volumes are now being published along with the present monograph. One, A Newly Discovered Greek Father, Cassian the Sabaite Eclipsed by John Cassian of Marseilles (folia 1r-118v). Two, An Ancient Commentary on the Book of Revelation: A Critical Edition of the Scholia in Apocalypsin . These Scholia were falsely attributed to Origen a century ago, but their real author is Cassian the Sabaite mainly drawing on a lost commentary on the Apocalypse by Didymus the Blind, as well as on Origen, Theodoret, Clement of Alexandria, Irenaeus, and others (folia 210v-290r).